Classification schemes used by public elementary school libraries in Quezon City - Canoza, Ronaldo O. (2006)
For most assigned librarians of public elementary schools, implementing a classification scheme is hard to do because they do not have any librarianship background and that they are not professionally trained. Thus, they resort to their own means of classifying and organizing their collection. The implementation of a classification scheme is an important activity in maintaining the library's effectiveness in imparting knowledge and entertainment to its patrons. It acts as a bridge between the books and the clients. That said, using a case study approach, the study aims to know what classification scheme is most recommendable to be used by the said type of library personnel.